Boys adrift : the five factors driving the growing epidemic of unmotivated boys and underachieving young men - Sax, Leonard (New York : Basic Books, 2016)
An updated version of his best seller, Sax delves into the scientific literature and draws on his vast clinical experience to propose an entirely original view of why boys and young men are continuing to fail in school and at home. He argues that a combination of social, cultural, and biological factors is creating an environment that is literally toxic to boys, ranging from environmental estrogens to the over-prescription of ADHD drugs. And he presents practical solutions-- from new ways of controlling boys' use of video games, to innovative (and workable) education reforms.
The riddle -- The first factor : changes at school -- The second factor : video games -- The third factor : medications for ADHD -- The fourth factor : endocrine disruptors -- End result : failure to launch -- The fifth factor : the revenge of the forsaken gods -- Detox.
Hardcover originally published in 2007 by Basic Books.
Includes bibliographical references (pages 279-331) and index.
Keywords: Boys -- Education; Young men -- Education; Motivation in education; Sex differences in education